Ginkgolide B Alleviates Learning and Memory Impairment in Rats With Vascular Dementia by Reducing Neuroinflammation via Regulating NF-κB Pathway - Huang, Lijuan; Shi, Yijie; Zhao, Liang (Frontiers in Pharmacology, 2021)
Ginkgobalide B (GB) as the main active ingredient of traditional Chinese medicine Ginkgo biloba extract is reported to reduce neuroinflammation, protect neurons and promote cognitive learning ability. To explore that GB can reduce neuroinflammation through regulating nuclear factor-kappaB (NF-κB) signaling pathway and overcome cognitive dysfunction in rats with vascular dementia (VD). In this study, we aim at investigating the potential effect of GB for enhancing cognitive function in rats with VD. It was found that GB improved survival of oxygen-glucose deprivation (OGD) treated SH-SY5Y cells by attenuating inflammatory response via Toll-like Receptor 4 (TLR4)/ NF-κB pathway. A rat model of bilateral common carotid artery occlusion (BCCAO) was established. After occlusion for 24 h, saline and GB were administered in Sprague-Dawley (SD) rats via a single intraperitoneal injection for consecutive 14 days. The behavioral changes of VD rats treated with GB were observed through open field test, Morris water maze (MWM) and Y-maze electric maze. Nissl staining and immunofluorescence were used to observe changes of neurons in the hippocampus of rats. Western blot analysis was performed by detecting NF-κB pathway related inflammatory factors. The results found that GB can significantly improve the learning and memory ability of VD rats by reducing TLR4/NF-κB mediated neuroinflammation. GB has become a potential drug for amelioration of learning and memory impairment in rats with VD.